Optimizing CPR performance with CPR coaching for pediatric cardiac arrest: A randomized simulation-based clinical trial. (November 2018) - Cheng, Adam; Duff, Jonathan P.; Kessler, David; Tofil, Nancy M.; Davidson, Jennifer; Lin, Yiqun; Chatfield, Jenny; Brown, Linda L.; Hunt, Elizabeth A.; ,
Abstract: Aim: To determine if integrating a trained CPR Coach into resuscitation teams can improve CPR quality during simulated pediatric cardiopulmonary arrest (CPA). Methods: We conducted a multicenter, prospective, randomized trial. An 18-minute simulated CPA scenario was run for resuscitation teams comprised of CPR-certified professionals from four International Network for Simulation-based Pediatric Innovation, Research & Education (INSPIRE) institutions. Forty teams (200 participants) were randomized to having a trained CPR Coach vs. no CPR Coach. CPR Coaches were responsible for providing real-time verbal feedback of CPR performance to compressors. All teams utilized CPR feedback technology. We report the proportion of overall excellent CPR, proportion of chest compressions (CC) with depth 50–60 mm, the proportion of CC with rate 100–120 per minute, CC fraction, and pre-, post-, and peri-shock pause duration. Results: CPR coached teams compared with teams without a CPR Coach resulted in an absolute improvements in overall excellent CPR by 31.8% (95% CI, 17.7, 35.9; p < 0.001), mean CC depth compliance by 31.5% (15.7, 47.4; p < 0.001), mean CC depth by 4.6 mm (1.6, 7.5; p < 0.001), mean CC fraction by 5.4% (0.2, 10.6; p = 0.04), and mean pre-, post- and peri-shock pause duration by −2.7 s (−5.1, −0.4; p = 0.02), −1.0 s (−1.8, −0.2; p = 0.01); and −3.8 (−6.6, −1.0; p = 0.008), respectively. Changes in mean CC rate compliance and mean CC rate were not statistically significant. Conclusions: In the presence of CPR feedback technology, the integration of a trained CPR coach into resuscitation teams enhances CPRquality metrics associated with improved survival outcomes from pediatric cardiac arrest.